Peran E-commerce dalam Meningkatkan Ekonomi Kreatif Sarung Tangan GloviSto di Shopee - Syahputra, Aldi; Nabillah, Nabillah; Luqyana, Syifa Febriani; Pramono, Pramono (Universitas Bumigora, 2025)
The advancement of e-commerce in Indonesia provides significant opportunities for MSMEs to enhance competitiveness and expand market reach, particularly in the creative economy sector. This study aims to explore the role of the Shopee platform in supporting the development of innovative products, such as GloviSto motorcycle gloves. The research employs a qualitative-descriptive method, collecting data through interviews with business owners, consumer surveys, and analysis of sales reports and Shopee features. The findings reveal that e-commerce facilitates market access and drives sales growth. Shopee features, such as Shopee Live, promotional discounts, and customer reviews, significantly influence product visibility and consumer trust. However, high competition and platform commission fees remain challenges for business operators. The study concludes that e-commerce serves as a strategic tool in developing the creative economy, not only by increasing MSME revenue but also by creating local employment opportunities. Recommendations for GloviSto include optimizing the use of Shopee features, expanding digital marketing strategies, and building collaborations with influencers to strengthen product competitiveness. Keywords: creative economy, e-commerce, motorcycle gloves